Swimming through asymmetry: zebrafish as a model for brain and behavior lateralization - Alessandra Gobbo; Andrea Messina; Giorgio Vallortigara (Frontiers in Behavioral Neuroscience)
The left and right sides of the brain show anatomical, neurochemical and functional differences. In the past century, brain and behavior lateralization was considered a human peculiarity associated with language and handedness. However, nowadays lateralization is known to occur among all vertebrates, from primates to fish. Fish, especially zebrafish (Danio rerio), have emerged as a crucial model for exploring the evolution and mechanisms of brain asymmetry. This review summarizes recent advances in zebrafish research on brain lateralization, highlighting how genetic tools, imaging, and transgenic methods have been used to investigate left–right asymmetries and their impact on sensory, cognitive, and social behaviors including possible links to neurodevelopmental and neurodegenerative disorders.